„Moja sztuka jest córką baroku i psychodelii” – twórczość Guillerma Péreza-Villalty w kontekście zjawiska kiczu - Pięcińska, Anna (Załącznik Kulturoznawczy, 2023)
The aim of this paper is to present the silhouette of Guillermo Pérez-Villalta, one of the most important contemporary artists in Spain, in the context of the idea of kitsch. The key question for one who would like to study Pérez- -Villalta’s pictures is the problem of the coexistence of the negatively regarded component like kitsch and the real respect for the painter treated as one of the most important figures of art in his country. What may seem even more curious is that Pérez-Villalta himself declares a really positive attitude to kitsch – he even says about being fascinated with it. This fascination may have its origins in the ideas represented by the socio-cultural movement from the 70-80s 20th century – la movida madrileña – that Pérez-Villalta was one of the co-founders. Movida was very keen on fun, laugh, colors and kitsch as well. Villalta painted two very important pictures then – Grupo de personas en un atrio o la alegoría del arte y la vida o del presente y el futuro(1975) and Escena, personajes en la salida de un concierto rock (1979), trying to show the relationships between the members of movida. Even now it is easy to find the elements of kitsch in Pérez-Villalta’s pictures but it does not in any way deny his originality and high position among contemporary Spanish most venerated artist.